Comparative Effects of Argumentation and Laboratory Experiments on Metacognition, Attitudes, and Science Process Skills of Primary School Children - Jale Kalemkuş; Şule Bayraktar; Sabahattin Çiftçi (Universitas Pendidikan Indonesia, 2021)
The purpose of this study is to investigate and compare the effects of laboratory experiments and argumentation-based science teaching on science process skills, metacognitive awareness levels, and attitudes towards science of 4th-grade elementary school students. In this study conducted according to the quantitative research method, a pre-test and post-test quasi-experimental design were used with two experimental groups and a control group. Students from three classes of an elementary school participated in the study (N = 98).